A Case of Disseminated Infection Caused by Streptococcus equi Subspecies zooepidemicus - Marie-France Poulin; Guy Boivin (Canadian Journal of Infectious Diseases and Medical Microbiology)
Human infections with Streptococcus equi subspecies zooepidemicus, a group C streptococcus, are very rare and are generally associated with contact with horses, and consumption of unpasteurized milk products, goat cheese or pork. In most cases S zooepidemicus leads to fulminant infections. The case of a middle-aged woman who had sporadic contact with horses is described in the present report. She developed a bacteremia with severe and extensive complications that included meningitis, mitral endocarditis and blindness due to bilateral endophthalmitis. To the authors’ knowledge, this is the first reported case of an endophthalmitis due to S zooepidemicus. Because of a penicillin allergy, the patient was treated with ceftriaxone and rifampin over six weeks and survived. The present case report highlights the severe complications associated with S zooepidemicus infection.